2016
DOI: 10.1002/cbf.3190
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of long non‐coding RNAs in hyperoxia‐induced bronchopulmonary dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) is a common complication of premature birth that seriously affects the survival rate and quality of life among preterm neonates. Long non-coding RNAs (lncRNAs) have been implicated in many human diseases. However, the role of lncRNAs in the pathogenesis of BPD remains poorly understood. Here, we exposed neonatal C57BL/6J mice to 95% concentrations of ambient oxygen and established a mouse lung injury model that mimicked human BPD. Next, we compared lncRNA and messenger RNA (mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Subsequently, however, genome wide association studies were unable to identify single nucleotide polymorphisms significantly associated with an increased risk of BPD 165, 166 . Additional screens to detect epigenetic marks 167 and changes in long non-coding RNA 168 , have recently been performed, and others such as proteomic and metabolomic screens, have not yet been undertaken. Although these advances in high throughput, ‘omic’ technologies can yield vast amounts of data, heterogeneity in the diseased population and the presence of multiple confounding factors can limit the power to differentiate true signals from background noise.…”
Section: Understanding Bpd Pathobiology – Future Directionsmentioning
confidence: 99%
“…Subsequently, however, genome wide association studies were unable to identify single nucleotide polymorphisms significantly associated with an increased risk of BPD 165, 166 . Additional screens to detect epigenetic marks 167 and changes in long non-coding RNA 168 , have recently been performed, and others such as proteomic and metabolomic screens, have not yet been undertaken. Although these advances in high throughput, ‘omic’ technologies can yield vast amounts of data, heterogeneity in the diseased population and the presence of multiple confounding factors can limit the power to differentiate true signals from background noise.…”
Section: Understanding Bpd Pathobiology – Future Directionsmentioning
confidence: 99%
“…The association of rare variants with BPD has been evaluated through multiple exome sequencing studies, which have suggested a role for kinase A- and mitogen-activated protein (MAP) kinase-related pathways in BPD (1315). To date, microarray-based gene expression studies of BPD have been performed on both blood and lung tissue samples collected from infants and from animal models and have identified several thousand genes as potentially being differentially expressed in BPD (1619). These studies reported that pathways involved in the inflammatory response are downregulated in BPD infants, while pathways related to the cell cycle are upregulated (18).…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48] In a recent report, researchers have screened differentially expressed lncRNAs in a hyperoxia-induced neonatal mouse BPD model, indicating that lncRNAs might participate in BPD development. 49 MALAT1, one lncRNA, is involved in several physiopathological process including angiogenesis, 50 diabetes progression, 51 tumour progression, 52 cardiovascular remodelling 53 and tissue inflammation. 19 It can play multiple roles, like promoting protein localization, acting as a competing endogenous RNA, or regulating protein activity, gene transcription and epigenetic changes.…”
Section: Dozens Of Lncrnas Can Regulate Gene Expression In Variousmentioning
confidence: 99%